Migratory motivations of American professional basketball players in Japan, Spain and Australia - Chiba, N. (Asia Pacific Journal of Sport and Social Science, 2013)
This study focuses on the overseas migratory motivation of American players in the world of professional basketball. Qualitative interviews were used to understand the experiences of eight American basketball players and the study adopts neo-classical economics as its theoretical framework. A total of six players attached importance to getting a good contract as professional players. One player emphasized the desire to experience a different culture. Another player had emigrated to continue playing basketball at a high-level and enjoy a comfortable life style. By demonstrating that many American players migrate to overseas countries because of disparities in salary between professional basketball leagues, the study provides evidence of the relevance of neo-classical economics to the motivations of professional basketball players in the international market.